Clinical spectrum of paediatric HIV infection in a tertiary care centre in South India - K. K., Santhosh Kumar; D., Narayanappa; M. D., Ravi; K., Jagadish Kumar (International Journal of Contemporary Pediatrics, 2018)
Background: The global burden of paediatric HIV and acquired immune deficiency syndrome (AIDS) remains a challenge for healthcare workers around the world, particularly in developing countries. The objective of this study is to describe the spectrum of HIV infection in children including the mode of transmission, clinical manifestations and opportunistic infections associated with HIV infection. Methods: Confirmed HIV seropositive children aged between 18 months to 19 years admitted to paediatric ward of JSS hospital, Mysore during two-year period were enrolled in this prospective observational study. Detailed history, socio-demographic characteristics and clinical manifestations were recorded in the predesigned performa. Nutritional assessment, complete physical, systemic and neurological examination was performed at the time of admission and was supplemented with ancillary investigations. Patients were correlated with modified WHO clinical case definition for AIDS and categorized as per revised CDC NABC classification of pediatric HIV infection. Results: Forty HIV-infected children were enrolled: with mean age of 4.5 years. Vertical transmission was the predominant mode of HIV transmission (97.5%). Most of the children were severely symptomatic belonging to category-C of NABC classification. Common clinical manifestations noted were failure to thrive (45%), recurrent respiratory infections (42%), bacterial skin infection (36%), recurrent otitis (42.5%), papulo-pruritic dermatitis (22%), hepatosplenomegaly (85%), lymphadenopathy (45%) and HIV encephalopathy (52%). The common opportunistic infections observed were pulmonary tuberculosis (45%), recurrent diarrhoea (35%), oral candidiasis (30%). The rare presentations of HIV noted were chronic thrombocytopenia and a case of dilated cardiomyopathy. Conclusions: Vertical transmission was the major route of HIV infection. HIV encephalopathy was more common among severely affected children. Tuberculosis was the commonest opportunistic infection.